Estrogen Inhibits Colon Polyp Formation by Reducing Angiogenesis in a Carcinogen-Induced Rat Model - Jia Yang; Li-juan Xiong; Fei Xu; Xiang Zhao; Bo Liu; Kai-Lin Cai; Guo-bin Wang (International Journal of Endocrinology)
Objective. To study the effects of estrogen on colon polyp formation, proliferation, and angiogenesis on a rat model of colon cancer induced by dimethylhydrazine (DMH). Methods. Thirty-six female ovariectomized (OVX) rats were randomly divided into 3 groups: (I) control group (administrated with vehicles weekly), (II) DMH group (administrated with DMH weekly), and (III) DMH + E2 group (administrated with DMH and 17β-estradiol weekly). The incidence, volumes, and multiplicity of colon polyps in each group were evaluated. The microvessel density (MVD), the expressions of Proliferating Cell Nuclear Antigen (PCNA), and the expressions of HIF-1α and VEGF in polyps were detected in each group. Results. Estrogen reduced the multiplicity, volumes, and the PCNA expressions of DMH-induced colon polyps. The MVD in DMH + E2 group was significantly lower than that in DMH group. Estrogen treatment decreased the HIF-1α and VEGF expressions at both mRNA and protein level. Conclusion. Estrogen replacement was protective for ovariectomized rats from DMH-induced carcinogenesis, and one of the mechanisms for this was due to estrogen’s inhibitive effects on blood vessel formation by downregulating VEGF and HIF-1α expressions.